Social determinants of health and the International Monetary Fund - Subramanian, S. V.; De Neve, Jan-Walter (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Education is considered an important social determinant of health (1, 2). Higher levels of educational attainment appear to be health-enhancing for those who have them (3), and provide intergenerational health benefits for their children (4) as well as their parents (5). Increased knowledge and skills leading to higher wages, as well as psychosocial advantages, such as social standing and control beliefs, are posited as mechanisms that link higher education and improved health (1, 2). In the context of low- and middle-income countries (LMICs), parental education (maternal in particular) is often held as a solution to improve children’s health (6). Meanwhile, a substantial number of governments in LMICs face considerable economic challenges, such as low macroeconomic growth, price instability, balance of payments crises, and high inflation, leading to their adoption of the International Monetary Fund’s (IMF) structural conditionality programs (hereafter, IMF-programs) (7). In exchange for the IMF’s low-cost lending and technical assistance, recipient governments must agree to implement a number of conditionalities, such as increased debt management, privatization of state-owned enterprises, trade liberalization, labor reforms, and anticorruption measures (8). It has been argued that IMF-programs not only directly impact health outcomes adversely, but also indirectly, by altering the influences of social determinants of health (8). In PNAS, Daoud et al. (9) provide a cross-sectional assessment of whether the protective relationship between the educational attainment of the household head (hereafter, education) and child severe malnutrition, lack of access to health services, sanitation, shelter, and water are attenuated in countries that have been exposed to IMF-programs compared with countries not exposed to IMF-programs during the period 1992-2007. Daoud et al. (9) collectively refer to these outcomes as child health, even though the outcomes are a combination of child health (e.g., malnutrition) and household (e.g., access to water) outcomes, with the …